Characteristics of exemplary teachers and their practices in Malaysia international Islamic school from da'wah perspective / Ahmed Elsaid Ahmed Elfarses - Ahmed Elsaid , Ahmed Elfarses (2022)
This study, themed Characteristics of Exemplary Teachers and Their Practices in Malaysia International Islamic School from Da'wah Perspective, Studyapplied to IGCSE students at International Islamic Schools in Selangor with special focus on Baseerah International Schools, International Islamic Schools, and Adni International Islamic Schools. The study uses descriptive and analytical method in order to define the problem. It draws theorical data from a number of literatures: references, periodicals and from field-based studies. The study uses questionnaire as a tool that consists of three sections: Section One contains variables (gender, grade, school). Section Two comprises two variants: personality traits and ethical qualities. Section Three is of two variables for assessing professional traits: teaching performance as well as teaching and evaluation methods. The research tool is applied to a focused sample and its data is analysed via appropriate statistical methods - SPSS. The study has reached several findings: That the teacher’s performance is of a highest concern by the students as they ticked (strongly agree) under the respective variable of the questionnaire. Thus, shows the extent to which students are aware of the importance of teacher’s performance in addition to how they are devoted to benefit from their expertise. That there are no statistically significant variations that could be attributed to gender or grade as regards the degree to which the traits of the role model teacher are displayed by teachers at international Islamic schools. The study offers some suggestions: that the concept of good role model should be introduced and integrated into academic curricula and syllabuses at all educational levels; that media of all types must display a role model teacher as positive and highly respected figure, not as a preposterous and laughable stock. Media of all types must credit role models in all domains: in Da’wah, sport, medicine, etc...; they must highlight their significant role in societies.